Mechanical Properties of Biocomposite with Various Composition of CaCO3 and Starch - Setiawan, Agris; Wahyuningsih, Fransisca Diana; Mirahati, Riria Zendy (Journal of Mechanical Engineering Science and Technology (JMEST), 2023)
Calcium carbonate has the potential to be used in the development of medical materials, including biomaterials. Biocomposite is composed of CaCO3 as matrix material and bioplastic from the combination of corn starch and cassava starch as reinforcement. This study aims to determine mechanical properties such as tensile strength and bending/flexural strength with varying compositions of CaCO3 and bioplastic. Characterization of the biocomposite uses Scanning Electron Microscope to observe the microstructure and composition elements of their structure. This study used 4 variations in the ratio of CaCO3 suspension: (Corn Starch + Cassava Starch). Each sample was characterized using specimen code A for composition 30:70 (w/w) percent and specimen B for composition 40:60 (w/w) percent, specimen C for composition 50:50 (w/w) percent, and specimen D for composition 60:40 (w/w) percent. Based on the results of shrinkage measurements on flexural strength specimens, specimen B has the lowest percentage value of 15±0.01 percent. The lowest tensile strength specimen is found in specimens C and D at 12±0.01 percent. The tensile test results also showed that specimen D had a higher ultimate strength value than the other specimens, which was 0.06±0.03 MPa. Microstructure characterization was carried out using scanning electron microscopy with energy-dispersive X-ray spectroscopy, which revealed the presence of Oxygen at approximately 48.39 percent mass, Carbon at approximately 30.27 percent mass, Nitrogen at approximately 11.77 percent mass, Calcium at approximately 9.57 percent mass, with Calcium being detected in the form of Calcium Carbonate (CaCO3).